2008
DOI: 10.1021/es702404g
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Decomposition of Vaporized Hydrogen Peroxide for Biological Decontamination of Galvanized Steel Ducting

Abstract: The behavior of vaporous hydrogen peroxide (VHP) was examined in clean, room-scale galvanized steel (GS) and polyvinylchloride-coated steel air ducts, to understand how it might be used to decontaminate larger ventilation systems. VHP injected into the GS duct decreased in concentration along the length of the duct, whereas VHP concentrations in the polyvinylchloride coated duct remained essentially constant, suggesting that VHP decomposed at the GS surface. However, decomposition was reduced at lower temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The decomposition can be minimized by increasing temperature, flow rate, and initial concentration; however, lower decomposition will result in a slower killing of the biological (Verce et al, 2008). Additionally, studies have found that the reduction of organisms using hydrogen peroxide gas is impacted by the porous and nonporous nature of the surfaces (Rogers et al, 2005).…”
Section: Decontamination Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decomposition can be minimized by increasing temperature, flow rate, and initial concentration; however, lower decomposition will result in a slower killing of the biological (Verce et al, 2008). Additionally, studies have found that the reduction of organisms using hydrogen peroxide gas is impacted by the porous and nonporous nature of the surfaces (Rogers et al, 2005).…”
Section: Decontamination Methodsmentioning
confidence: 99%
“…Surface softening was slight and confined to the immediate vicinity of the surface, necessitating further work (Gale et al, 2009). Studies have shown minimal oxidative damage after 100 experiments over one year, but there was a patina on the surfaces area where the VHP was introduced (Verce et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaporized hydrogen peroxide treatments have been investigated for possible usage in disinfection/decontamination of buildings [6], spacecraft [7], aircraft [8,9] and railcars [10]. The aircraft studies used vaporized hydrogen peroxide concentrations in the range of 150-600 ppm and cycle times of 80-120 min.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide is considered less toxic to humans than other fumigants (e.g., formaldehyde, chlorine dioxide); therefore, it has been widely used to treat laboratory and medical equipment, pharmaceutical facilities, hospital rooms, ambulances, animal holding rooms, and air ducts (Anderson et al, 2006;Dryden et al, 2008;Fichet et al, 2004;French et al, 2004;Heckert et al, 1997;Hillman, 2004;Johnston et al, 2005;Klapes & Vesley, 1990;Krause et al, 2001;;Krishna et al, 2000;Verce et al, 2008;Wagenaar & Snijders, 2004). The use of hydrogen peroxide as a fumigant, dry mist, or an aqueous solution promotes decontamination efficacy against a wide range of microorganisms, including bacterial spores, vegetative bacteria, fungi, viruses, and bacteriophages (French et al, 2004;Grare et al, 2008;Hall et al, 2007;Hall et al, 2008;Heckert et al, 1997;Hillman, 2004;Johnston et al, 2005;Klapes & Vesley, 1990;Melley et al, 2002;Otter & Dudde-Niekiel, 2009;Rastogi et al, 2009;Rogers et al, 2005;Rogers et al, 2008b;Rogers & Choi, 2008).…”
Section: Introductionmentioning
confidence: 99%